2014
DOI: 10.1021/es4042836
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Biodegradation Patterns of Persistent Saturated Hydrocarbons in Weathered Oil Samples from the Deepwater Horizon Disaster

Abstract: Biodegradation plays a major role in the natural attenuation of oil spills. However, limited information is available about biodegradation of different saturated hydrocarbon classes in surface environments, despite that oils are composed mostly of saturates, due to the limited ability of conventional gas chromatography (GC) to resolve this compound group. We studied eight weathered oil samples collected from four Gulf of Mexico beaches 12-19 months after the Deepwater Horizon disaster. Using comprehensive two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 68 publications
9
101
0
Order By: Relevance
“…15,18,20,23 The environmental fate of the sand patties was explored and documented in Chapter 1. It was found that photooxidation and aerobic biodegradation were significant advanced weathering processes impacting the stability of these structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,18,20,23 The environmental fate of the sand patties was explored and documented in Chapter 1. It was found that photooxidation and aerobic biodegradation were significant advanced weathering processes impacting the stability of these structures.…”
Section: Discussionmentioning
confidence: 99%
“…Since sand patties originate from spilled oil and contain a variety of hydrophobic compounds 15,18,21,23 there is a tendency to assume that these structures resist the 4 and heat maps were generated using the associated imaging software.…”
Section: Seawater Transport In Sand Pattiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For sparingly soluble hydrocarbons, biodegradation is expected to serve as the primary cause of weathering in the deep ocean because other key weathering processes (e.g., evaporation, photooxidation) depend on atmospheric and solar exposure. Although hydrocarbon recalcitrance to biodegradation is expected to scale roughly with molecular mass and steric complexity (32), the rates at which specific hydrocarbons are metabolized vary based on myriad environmental variables: temperature, salinity, pressure, oxygen concentration, pH, solar exposure, availability of nutrients and other sources of organic matter (33), water availability, access to substrate, solid-phase interactions, competition, predation, and inhibition (34). Although early reports addressed the degradation of some low-to moderate-molecular-mass compounds in the water column (12,14,16), the degradation rates of the petroleum hydrocarbons constituting Macondo oil after seafloor deposition are unknown.…”
Section: Significancementioning
confidence: 99%